A Study on Exploring the Concept of Social Entrepreneurship - CHOUDHARY, ANAND (IJRDO - Journal of Business Management, 2019)
Social entrepreneurship in recent times has gained importance as a means to meet social and economic needs of the poor globally. However, in spite of it’s increasing popularity as a concept, there is no consensus among academics and practitioners when it comes to formulating one common definition on the topic which may be acceptable to all as it means different things to different people. The current article tries to analyse the literature available on the subject, exploring it’s theoretical and conceptual framework which helps to understand the phenomena of social entrepreneurship and its role, importance and applicability in the modern society.